2005
DOI: 10.1016/s1808-8694(15)31263-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inspiratory pressure in children with enlarged tonsils and adenoids

Abstract: Enlarged tonsils and adenoids were associated with poor inspiratory pressure, resulting in increased breathing effort and work of the involved muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
0
12
0
3
Order By: Relevance
“…Another factor that might affect respiratory biomechanics is the lower respiratory effort required by mouth breathing, as well as the inhibition of the nasal afferent nerves, responsible for regulating lung capacity and lung volumes, resulting in poor use of the respiratory muscles and progressive muscle weakening. (8,21,22) We found reduced respiratory muscle strength in the MB group. In a study evaluating the thoracic perimeter of mouth breathing children, lower values were found in relation to the control group.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Another factor that might affect respiratory biomechanics is the lower respiratory effort required by mouth breathing, as well as the inhibition of the nasal afferent nerves, responsible for regulating lung capacity and lung volumes, resulting in poor use of the respiratory muscles and progressive muscle weakening. (8,21,22) We found reduced respiratory muscle strength in the MB group. In a study evaluating the thoracic perimeter of mouth breathing children, lower values were found in relation to the control group.…”
Section: Discussionmentioning
confidence: 58%
“…(21,22) In cases that are more severe, this can be accompanied by obstructive sleep apnea syndrome or cor pulmonale. (18) According to another hypothesis, known as the one-airway hypothesis, the effect of CMB can extend to the lung region and interfere with the physiological response to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsils grade 0, 1 and 2 were considered as non-obstructive and those classified as grade 3 and 4 were named as obstructive [18].…”
Section: Ent Data Collectionmentioning
confidence: 99%
“…In a previous paper we found that children with tonsil and adenoid enlargement present lower maximal inspiratory pressure when compared to a control group [7].…”
Section: Discussionmentioning
confidence: 80%